2008
DOI: 10.1002/adma.200800932
|View full text |Cite
|
Sign up to set email alerts
|

Optically Responsive and Mechanically Tunable Colloid‐In‐Liquid Crystal Gels that Support Growth of Fibroblasts

Abstract: Whereas low molecular weight liquid crystals (LCs) are too soft to support the culture of fibroblast cells, gels formed by polystyrene microparticles dispersed in LCs can be mechanically tuned to support the cell culture. These self‐supporting gels can be readily molded, thus facilitating their use for cell culture, and they contain micrometer‐sized domains of LCs that can be oriented by interactions at the surfaces confining the gels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 27 publications
(61 reference statements)
1
60
0
Order By: Relevance
“…Additionally, several studies have investigated the impact that contact with various LCs has on the viability of cells [107-109] and microorgansisms [109, 110]. In particular, it was found that LC interfaces can be used to support the growth of cells [111, 112]. Such LC-based substrates may have utility in reporting interactions with cells.…”
Section: Lcs As Sensors Of Viruses Bacteria and Mammalian Cellsmentioning
confidence: 99%
“…Additionally, several studies have investigated the impact that contact with various LCs has on the viability of cells [107-109] and microorgansisms [109, 110]. In particular, it was found that LC interfaces can be used to support the growth of cells [111, 112]. Such LC-based substrates may have utility in reporting interactions with cells.…”
Section: Lcs As Sensors Of Viruses Bacteria and Mammalian Cellsmentioning
confidence: 99%
“…E7 is a mixture of four alkoxycyanobiphenyls (nCBs) with different aliphatic chain length: 51 wt.% 4-cyano-4'-n-pentyl-biphenyl (5CB), 25 wt.% 4-cyano-4'-nheptyl-biphenyl (7CB), 16 wt.% 4-cyano-4'-noxyoctyl-biphenyl (8OCB) and 8 wt.% 4-cyano-4'-n-pentyl-p-terphenyl (5CT). Agarwal et al, (2008) and Pal et al, (2009) demonstrated that when colloidal suspensions of microspheres are prepared in the isotropic phase of LCs followed by cooling below their isotropic-nematic transition temperature (T NI ), they form birefringent waxy semi-solid (gel) with significant storage modulus (G'~10 3 -10 5 KPa). This gelation has been suggested to result from the formation of a particle network resulted from expulsion of colloids from the nematic LC as it cools down from isotropic to nematic phase.…”
Section: Colloidal Liquid Crystal Gels For Biomolecular Amplificationmentioning
confidence: 99%
“…Whereas the commonly used nematic 5CB, other synthetic LCs and other phase (cholesteric) [69] or type (lyotropic) [70] of LCs offer a rich pool for exploration and provide more versatile properties. Taking advantage of emerging fabrication techniques, it is shown that low molecular weight LCs can be tailored to form a gel-like material with tunable mechanics [71], which promises a possibility of using LCs to culture mammalian cells (which are sensitive to substrate stiffness) [72] and reporting the interactions between cells and substrates. In addition, LCs with the orientational alignment and anisotropic mechanical properties might be a good candidate for directing neurite branching [73,74] and promoting stem cell differentiation, etc.…”
Section: Discussionmentioning
confidence: 99%